The role and significance of a perliamentery democracy in the development of the Bulgarian society - Бурдяк, Віра (My University, 2014)
The author of the paper analyzes the parliamentary democracy in the Republic of Bulgaria and considers it to be the important factor of community development. The parliamentary system of Bulgaria depicts the idea of rational parliamentarianism, when the constitutional system has judicial techniques to keep stability and power of the government when there is no parliamentary majority. The relationship between the government and parliament is revealed in their cooperation in carrying out the functions of each other and controlling each other’s work. The Bulgarian parliament controls the government’s activity by means of classical techniques of requests and inquiries.
Keywords: The republic of Bulgaria; democratization; parliament; opposition; president; political authoritative institutions; bodies of powers; lawmaking; right of legislative initiative